Degrading Boko Haram Terrorism in the Muhammadu Buhari Era: Issues and Realities - OPEYEOLUWA, Rotimi Olajide; Balogun, Noah Opeyemi (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
The continuing haemorrhagic nature of Boko Haram calls for an exhaustive discourse on the veracity or otherwise claim of President Buhari’s government of “technically defeating” the terrorist group as quickly as possible once elected. This paper examines the evolving and sustained onslaught of Boko Haram terrorism in Nigeria against the backdrop of government insistence that the sect has been substantially degraded; the index to the contrary is worrying and alarming for the citizens to bear. This has thrown up a ferocious debate about the claim and counterclaim across the political divide and even the country in recent times. However, regardless of what opinion one holds, the sheer scale of the brutality of the sect after the government’s continuous claim that it has been degraded in the face of a sustained military offensive, both by ground forces and air interdiction operations imply that the sect is resilient and yet to be degraded. This paper, therefore, attempts to provide explanatory narratives on the prevalent realities and also opines that even though the counter-insurgency operation presaged the emergence of President Muhammadu Buhari; and having inherited the “war” more needs to be done in the immediate years of his presidency. That the Boko Haram sect continues to run rampage is simply unacceptable in the face of his campaign promise to defeat the sect within the shortest possible time of his ascendancy to the highest office in the land. The paper concludes that terrorism currently assailing the Nigerian state requires a critical examination with appropriate solutions rather than the government’s tepid claims that continues to be challenged by a sect that has evidently grown more audacious in the intervening years since it first evolved in 2009.